Isolation and Characterization of a New Allelochemical from Seeds of Adenanthera pavonina Linn. - Yadava, R.N.; Kumar Vishwakarma, Umesh (Asian Journal of Chemistry, 2013)
A new allelochemical (1), m.p. 282-284 ºC, m.f. C31H36O19, [M]+ 712 (FABMS), has been isolated from methanolic extract of the seeds of Adenanthera pavonina Linn. alongwith two known compounds 2',4',7-trihydroxy isoflavone and isovitexin. The structure of a new compound was characterized as 3,5,7,3',4'-pentahydroxy flavone-3'-O-a-L-rhamnopyranosyl-(1®4)-O-a-L-arabinopyranosyl-(1®3)-O-b-D-xylopyranoside, by various colour reactions, spectral analysis and chemical degradations.